Development of MIKIR E-Module Through Service-Learning Community Based Research - Darma Putra; Abul Walid; Try Susanti; Andi Asari (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an e-module based on MIKiR in improving students' mathematical abilities through the mathematical process and why it is necessary to develop and obtain a collaboration model of Lecturers, Teachers and Students in developing e-modules through community service-based research. This study is a RnD development research with the ASSURE model through Service-learning and Community Based Research (SLCBR). Based on the research results, it was concluded that (1) The importance of developing MIKiR e-modules through KKN community-based research, (2) The development of MIKiR e-modules through KKN community-based research produces valid and effective e-modules in facilitating active learning experiences, interaction, communication, and reflection (MIKiR), developing mathematical reasoning proof skills, representation connections, and communication (PRKoKo), and the mathematical process of inquiry-discovery and problem solving (PPPM), (3) The development of MIKiR e-modules through KKN community-based research produces practical e-modules in the form of ease of use of e-modules, efficiency of time use of e-modules, suitability to competencies, interesting, and can be used as independent learning, (4) The collaboration model of lecturers, teachers, and students in this research was designed based on the goals of each individual involved and what their respective responsibilities are in the research.